Handling Non-Performing Loans: Case Studies on Pt. BPR Supra Artapersada Cibeber Branch - Balqista, Nur Prasida; Sudarma, Ade; Kartini, Tina (Adpebi International Journal of Multidisciplinary Sciences, 2023)
People's Credit Bank is a banking institution that prioritizes lending services to the public. The distribution will be accompanied by credit risk, namely the emergence of non-performing loans. This study aims to determine the handling of non-performing loans at PT. BPR Supra Cibeber Branch. The research method used is to use qualitative methods by conducting observation techniques, in-depth interviews, and documentation. The results of the study showed an increase in NPL in 2022 by 1.37%, while the distribution of working capital decreased by 6.05%. In terms of handling non-performing loans PT. BPR Supra Artapersada Cibeber Branch implements several efforts, namely by conducting intensive visits to debtors, providing warning letters 1-3, making 3R efforts (Rescheduling, Reconditioning, Restructuring), taking over collateral, and writing off books for debtors.